2023
DOI: 10.1039/d2ra06834f
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on the biological efficacy of approved drugs and potent synthetic compounds against SARS-CoV-2

Abstract: The role of functional group in discovery of Nirmatrelvir is valuable and interesting for development of various inhibitors against viral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…As shown in Figure B, rings A and C of compound 1 effectively fill the S4 pocket formed by PRO 52, MET 165, ASP 187, HIS 41, ASN 53, and LEU 50, and productive hydrogen bonding to GLN 189 with occupancy of 29.8% (Table S3). Similarly, it is reported that the cocrystal compounds baicalein show hydrophobic interactions with the residues HIS 41 and MET 165 . Meanwhile, both PF-07304814 and PF00835231 were reported to form hydrogen-bonding interactions with residues GLN 189 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…As shown in Figure B, rings A and C of compound 1 effectively fill the S4 pocket formed by PRO 52, MET 165, ASP 187, HIS 41, ASN 53, and LEU 50, and productive hydrogen bonding to GLN 189 with occupancy of 29.8% (Table S3). Similarly, it is reported that the cocrystal compounds baicalein show hydrophobic interactions with the residues HIS 41 and MET 165 . Meanwhile, both PF-07304814 and PF00835231 were reported to form hydrogen-bonding interactions with residues GLN 189 .…”
Section: Resultsmentioning
confidence: 85%
“…The synthesized compounds such as PF-07321332 and PF-0083523 have been demonstrated to be potent inhibitors of the proteolytic activity of SARS-COV-2 Mpro . PF-07321332, named Nirmatrelvir, recently received approval for usage in conjunction with ritonavir . Remarkably, chemical ingredients originating from natural products, such as Traditional Chinese medicines (TCMs), Siddha Medicine, and Ayurvedic herbal formulations, have drawn increasing attention in the treatment of COVID-19 or inhibiting the target activities of SARS-CoV-2. By targeting SARS-CoV-2 Mpro, a considerable number of compounds derived from TCMs were identified.…”
Section: Introductionmentioning
confidence: 99%
“…The unique mechanism of action of this compound is expected to synergize with other leading anti-SARS-CoV-2 treatments, such as Molnupiravir and Nirmatrelvir. Infectious RNA viruses, such as Ebola and Marburg virus, cause serious lethal hemorrhage diseases [ 11 , 55 , 56 ] that have the potential to be pandemic; therefore, new drug candidates that are effective against RNA viruses are a global need. Further studies on the antiviral activity and mechanism of activity of Neoilludin B and its variants against these viruses can provide valuable anti-viral drug candidates to human disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several single-compound antivirals have shown themselves to be effective against SARS-CoV-2 in preclinical studies and are in clinical development [ 11 , 12 ]. However, these single-molecule-, single-target-based approaches may be challenging to implement effectively in rapidly evolving virus strains of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%